Making comics : storytelling secrets of comics, manga and graphic novels - McCloud, Scott, 1960- (New York : Harper, 2006)
Examines the concepts of comic writing, discussing clarity, persuasion, intensity, character design, facial expressions, body language, word choice, sense of place, tools, techniques, technology, style, and the professional comic writer. Presented in graphic novel format.
Includes bibliographical references (p. 256-257) and index.
Library Journal.
Pub Weekly.
School Library Journal.
Adult
Keywords: Cartooning -- Technique -- Comic books, strips, etc; Comic books, strips, etc. -- Authorship -- Comic books, strips, etc; Comic books, strips, etc. -- History and criticism -- Comic books, strips, etc; Cartooning -- Technique -- Comic books, strips, etc; Comic books, strips, etc. -- History and criticism -- Comic books, strips, etc; Comic books, strips, etc. -- Technique -- Comic books, strips, etc